Case–control study to assess the association between colorectal cancer and selected occupational agents using INTEROCC job exposure matrix. Issue 4 (8th December 2017) - El-Zaemey, Sonia; Anand, TN; Heyworth, Jane Shirley; Boyle, Terry; van Tongeren, Martie; Fritschi, Lin
Abstract : Background: Colorectal cancer is the third most prevalent cancer in the world and is twice as common in developed countries when compared with low-income and middle-income countries. Few occupational risk factors for colorectal cancer have been identified. This case–control study aimed to assess the association between colorectal cancer and occupational exposure to selected solvents, combustion products, metals, dusts and other agents. Methods: Cases (n=918) were enrolled from the Western Australian Cancer Registry from June 2005 to August 2007. Controls (n=1021) were randomly selected from the Western Australian electoral roll. We collected lifetime occupational history from cases and controls, in addition to their demographic and lifestyle characteristics. We applied the INTEROCC job exposure matrix to convert the occupational history to occupational exposure for 18 selected agents. Three exposure indices were developed: (1) exposed versus non-exposed; (2) lifetime cumulative exposure; and (3) total duration of exposure. The associations between colorectal cancer and the selected agents were estimated using logistic regression models adjusting for sex and age. Results: None of the 18 selected agents showed an association with colorectal cancer. No dose–response relationships with lifetime cumulative exposure or duration of exposure were observed. Conclusion: There was no evidence to suggest that occupational exposure to 18 selected agents increased the risk of colorectal cancer.